ANALISIS PERAMALAN DAN PERMINTAAN KREDIT SEKTOR PERTANIAN PADA PT.BRI (PERSERO) UNIT KEPAHIANG I - Badrudin, Redy; Sumantri, Bambang; Cecilia, Meiliza (Jurnal AGRISEP, 2004)
The study  was aimed to Know   growth and forecast the amount of demand for agricultural sector credit at PT. BRI (Persero) Unit Kepahiang I, and (2) examine factors influencing for agricultural sector credit. Data  was secondary data from 1993  up to 2003. Ratio  to Moving Average Method, Double Exponential Smoothing with moved period 3 monthly and regression function of Non Doubled Linear were used. Results of research indicates that growth of demand for agricultural credit at PT. SRI (Persero) Unit Kepahiang I tend to fluctuate. Forecasting of demand for agricultural sector creditb to period quarterly at 2003 till 2004, tend   to have experience decreasing significantly compare to previous period. Overall of factors influencing demand of agricultural sector is rate of interest level (X1), price level (X2), and agriculture product exchange rate (X3), while earning level (X4) does not have an effect on demand